Effect of degree of deformation on the mechanical properties of high temperature thermomechanically treated steel (2006)
The development of hgh strength materials, coupled with good formability, has always been the aim of material scientists. The effect of degree of deformation on the mechanical propehes of hgh temperature themomechanically treated steel (HTMT) has been investigated in this study. It has shown that an increase in percent deformation results in improvement in mechanical propehes. In order to have maximum strengthening, heavy deformation and low finishing temperature should be chosen.